METAPHYSICAL TRADITIONS IN MODERN POETRY - Xursanov Dilshod Baxtiyorovich (Western European Studies, 2025)
This article explores the continuity and transformation of metaphysical traditions in modern poetry through qualitative literary analysis. Using classical metaphysical poetry as a conceptual foundation, the study examines how modern poets adapt philosophical inquiry, complex metaphor, and introspective subjectivity to contemporary contexts. The findings show that although modern poetry moves away from theological certainty, it maintains a strong engagement with existential questions of being, identity, time, and meaning. Metaphysical elements are reconfigured through symbolic imagery and internalized reflection, demonstrating the enduring relevance of metaphysical thought as an evolving poetic mode within modern literary discourse.
Keywords: Metaphysical poetry; modern poetry; philosophical inquiry